2013
DOI: 10.1371/journal.pone.0058144
|View full text |Cite
|
Sign up to set email alerts
|

Levels of Lycopene β-Cyclase 1 Modulate Carotenoid Gene Expression and Accumulation in Daucus carota

Abstract: Plant carotenoids are synthesized and accumulated in plastids through a highly regulated pathway. Lycopene β-cyclase (LCYB) is a key enzyme involved directly in the synthesis of α-carotene and β-carotene through the cyclization of lycopene. Carotenoids are produced in both carrot (Daucus carota) leaves and reserve roots, and high amounts of α-carotene and β-carotene accumulate in the latter. In some plant models, the presence of different isoforms of carotenogenic genes is associated with an organ-specific fun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
80
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(97 citation statements)
references
References 71 publications
17
80
0
Order By: Relevance
“…Inhibition of PSY or PDS activity affects carotenoid content and results in a bleached phenotype due to the virtual absence of carotenoid compounds (Fray & Grierson, 1993;McCarthy et al, 2004;Qin et al, 2007). It has also been shown that overexpression of LCY-b in transgenic carrot lines results in the increased expression of PSY genes, suggesting a positive feedback effect controlling the carotenoid pathway (Moreno et al, 2013). Consistent with the increased expression of the carotenoid genes in the transgenic N. benthamiana plants, the transcriptomic analysis of AdMYB7infiltrated N. benthamiana leaves showed the upregulation of NbGGPPS, NbPSY, NbPDS, NbCRTISO and NbLCY-b.…”
Section: Myb7 Induced Expression Of Key Chl and Carotenoid Metabolic mentioning
confidence: 99%
“…Inhibition of PSY or PDS activity affects carotenoid content and results in a bleached phenotype due to the virtual absence of carotenoid compounds (Fray & Grierson, 1993;McCarthy et al, 2004;Qin et al, 2007). It has also been shown that overexpression of LCY-b in transgenic carrot lines results in the increased expression of PSY genes, suggesting a positive feedback effect controlling the carotenoid pathway (Moreno et al, 2013). Consistent with the increased expression of the carotenoid genes in the transgenic N. benthamiana plants, the transcriptomic analysis of AdMYB7infiltrated N. benthamiana leaves showed the upregulation of NbGGPPS, NbPSY, NbPDS, NbCRTISO and NbLCY-b.…”
Section: Myb7 Induced Expression Of Key Chl and Carotenoid Metabolic mentioning
confidence: 99%
“…b-LCY alone produces b-carotene whereas two enzymes, b-LCY and e-LCY (EC: 5.5.1.18), together form a-carotene (Beyer et al, 1991;Hornero-Méndez and Britton, 2002;Moreno et al, 2013). b-LCYs of plants and bacteria have a conserved dinucleotide binding motif. Furthermore, several conserved domains such as conserved region b-LCY's, b-LCY specific motif, cylase motif I and II (CMI and CMII), b-LCY CAD (catalytic activity domain) and a charged region are highly conserved in plants ( Moreno et al, 2013;Hugueney et al, 1995). b-LCY CAD is essential for b-LCY activity (Moreno et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, several conserved domains such as conserved region b-LCY's, b-LCY specific motif, cylase motif I and II (CMI and CMII), b-LCY CAD (catalytic activity domain) and a charged region are highly conserved in plants ( Moreno et al, 2013;Hugueney et al, 1995). b-LCY CAD is essential for b-LCY activity (Moreno et al, 2013). Cyclization of lycopene is formed by LYCs and conserved in various organisms (Armstrong et al, 1990).…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore conceivable that isoforms PSY1, ZDS1, and LCYB2 are mainly responsible for the production of carotenoids for photosynthesis and photoprotection (chloroplasts) whereas PSY2, ZDS2, and LCYB1 would be most involved in the biosynthesis of carotenoid in dark-grown carrot roots (chromoplasts). Recent work confirmed the involvement of LCYB1 in carotenoid biosynthesis in storage roots but also in leaves [44]. Further work will be required to define the specific role of all enzyme isoforms in carrot.…”
Section: Genes Encoding Most Of the Enzymes Involved In Carotenoid Bimentioning
confidence: 84%